2022
DOI: 10.3390/healthcare10061062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Educational Differences in the Risk of Cognitive Impairment: A Gender-Specific Analysis Using Korean Longitudinal Study of Aging (2006–2016)

Abstract: This study examined the effect of aging on gender-specific educational differences in the risk of cognitive impairment using a nationally representative sample of 4278 men and 5495 women aged 45 years and older from the dataset of the Korean Longitudinal Study of Aging. Sociodemographics, lifestyle, and medical conditions were included as covariates in the mixed logistic regression analysis models. The prevalence of cognitive impairment was higher in women than in men at baseline. The risk of cognitive impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…The demographics analysis showed that age and education were highly correlated with the K-MoCA score as previous studies have consistently shown [33][34][35]. Age independently accounted for close to 6% of MoCA score variance, whereas years of education accounted for almost 16% of the variation.…”
Section: Discussionsupporting
confidence: 61%
“…The demographics analysis showed that age and education were highly correlated with the K-MoCA score as previous studies have consistently shown [33][34][35]. Age independently accounted for close to 6% of MoCA score variance, whereas years of education accounted for almost 16% of the variation.…”
Section: Discussionsupporting
confidence: 61%
“…Brain health and age-related cognitive decline have been studied extensively. The course and extent of cognitive deterioration are influenced by various factors, such as lifestyle, education, genetics and cognitive engagement [ 57 , 58 ]. A recent study by Lin et al [ 58 ], using data of 17030 participants from the UK Biobank, identified several significant features that were meaningfully associated with brain and cognitive maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it has been frequently found that women are more likely than men to suffer from cognitive impairment [ 57 , 67 , 68 , 69 ]. Furthermore, an examination of 34 439 elderly individuals with normal cognition revealed that women might have greater cognitive reserve but faster cognitive decline than men [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Previous studies have shown that cognitive function can be influenced by various factors, including genetic and environmental factors. 4,5 Numerous studies have consistently identified age, education, sex, 6 health habits such as drinking and smoking, 7 depression, 8 sleep issues, 9 social factors (activity level and occupation), 9 and body mass index (BMI) 10 as factors affecting cognitive function among young adults. Identifying factors associated with cognitive decline might help in enhancing cognitive function through appropriate measures.…”
Section: Introductionmentioning
confidence: 99%